The Deployment of an Opposition: The Ex President Frei Montalva and the Dictator Pinochet in the Us Archives (1973-1982) - Ulianova, O (PONTIFICA UNIV CATOLICA CHILE, INST HISTORIA, 2014)
Using declassified US documents, this article examines the complex relationship between the Democracia Crisitana (PDC) Chile s largest political party and the Military Regime, between the years 1973 and 1982. The American idea of the PDC was primarily centered on its leaders, especially on the political figure Eduardo Frei Montalva. This article argues that American documents reveal that of Eduardo Frei Montalva s numerous interactions with the international community were to critique the Military Regime, which happened much earlier than it was supposed. The same documentation reveals that the regime s animosity and growing irritation with Frei s political activity in Chile and on the international scene, reached obsessive levels in trying to build a negative image of its main enemy.